Impact of diabetes on epicardial reperfusion and mortality in a contemporary STEMI population undergoing mechanical reperfusion: Insights from the ISACS STEMI COVID 19 registry - De Luca, Giuseppe; Algowhary, Magdy; Uguz, Berat; Oliveira, Dinaldo C; Ganyukov, Vladimir; Zimbakov, Zan; Cercek, Miha; Jensen, Lisette Okkels; Loh, Poay Huan; Calmac, Lucian; Roura I Ferrer, Gerard; Quadros, Alexandre; et al. (NMCD. Nutrition Metabolism and Cardiovascular Diseases, 2025)
BACKGROUND AND AIM: Diabetes has been shown in last decades to be associated with a significantly higher mortality among patients with ST-segment elevation myocardial infarction (STEMI) treated with primary PCI (PPCI). Therefore, the aim of current study was to evaluate the impact of diabetes on times delays, reperfusion and mortality in a contemporary STEMI population undergoing PPCI, including treatment during the COVID pandemic. METHODS AND RESULTS: The ISACS-STEMI COVID-19 is a large-scale retrospective multicenter registry involving PPCI centers from Europe, Latin America, South-East Asia and North-Africa, including patients treated from 1st of March until June 30, 2019 and 2020. Primary study endpoint of this analysis was in-hospital mortality. Secondary endpoints were postprocedural TIMI 0-2 flow and 30-day mortality. Our population is represented by 16083 STEMI patients. A total of 3812 (23,7 %) patients suffered from diabetes. They were older, more often males as compared to non-diabetes. Diabetic patients were less often active smokers and had less often a positive family history of CAD, but they were more often affected by hypertension and hypercholesterolemia, with higher prevalence of previous STEMI and previous CABG. Diabetic patients had longer ischemia time, had more often anterior MI, cardiogenic shock, rescue PCI and multivessel disease. They had less often out-of-hospital cardiac arrest and in-stent thrombosis, received more often a mechanical support, received less often a coronary stent and DES. Diabetes was associated with a significantly impaired postprocedural TIMI flow (TIMI 0-2: 9.8 % vs 7.2 %, adjusted OR [95 % CI] = 1.17 [1.02-1.38], p = 0.024) and higher mortality (in-hospital: 9.1 % vs 4.8 %, Adjusted OR [95 % CI] = 1.70 [1.43-2.02], p < 0.001; 30-day mortality: 10.8 % vs 6 %, Adjusted HR [95 % CI] = 1.46 [1.26-1.68], p < 0.001) as compared to non-diabetes, particularly during the pandemic. CONCLUSIONS: Our study showed that in a contemporary STEMI population undergoing PPCI, diabetes is significantly associated with impaired epicardial reperfusion that translates into higher in-hospital and 30-day mortality, particularly during the pandemic.
Keywords: výsledek terapie; diabetes mellitus; Diabetes Mellitus; hodnocení rizik; Male; retrospektivní studie; Middle Aged; Risk Assessment; Risk Factors; mortalita v nemocnicích; Aged; infarkt myokardu s elevacemi ST úseků; mužské pohlaví; senioři; ST Elevation Myocardial Infarction; registrace; Hospital Mortality; Treatment Outcome; Time Factors; Time-to-Treatment; lidé; ženské pohlaví; Humans; časové faktory; rizikové faktory; koronární angioplastika; Registries; Retrospective Studies; čas zasáhnout při rozvinutí nemoci; Female; lidé středního věku; Percutaneous Coronary Intervention; COVID-19